2018
DOI: 10.9734/jeai/2018/41164
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Nutrient Management in Aerobic Finger Millet (Eleusine coracana (L.) Gaertn) under Rainfed Agriculture

Abstract: The poor resource growers of southern Chhattisgarh have deprived of modern technologies of cultivation including externally managed inputs to augment the finger millet production. The low, negligible or no profit associated rainfed (aerobic) agriculture is still the only option owing to their socio-economic condition and physiographic location. The field experiment was conducted during the rainy (Kharif) seasons of 2011 and 2012 at Bastar district of Chhattisgarh with local finger millet (Eleusine coracana L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The authors opined that the regular consumption of finger millet will be effective in combating these life-threatening ailments. In another article, Pradhan et al (2010) found that the level of sugar in diabetic person was reduced with the continuous consumption of multigrain flour. Shobana et al (2013) provided a review about the historical relevance, consumption, processing, nutritional properties and health benefits of finger millets.…”
Section: Synthesizing the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The authors opined that the regular consumption of finger millet will be effective in combating these life-threatening ailments. In another article, Pradhan et al (2010) found that the level of sugar in diabetic person was reduced with the continuous consumption of multigrain flour. Shobana et al (2013) provided a review about the historical relevance, consumption, processing, nutritional properties and health benefits of finger millets.…”
Section: Synthesizing the Literaturementioning
confidence: 99%
“…In another article, Pradhan et al. (2010) found that the level of sugar in diabetic person was reduced with the continuous consumption of multigrain flour. Shobana et al.…”
Section: Synthesizing the Literaturementioning
confidence: 99%
“…[29] Catechin is one of the major antioxidant principles present. [30] It is endowed with health benefit such as hypocholestrolemic, hypoglycemic and antiulcerative [31] potency in inhibition of cataract development, [32] type 2 diabetes management, [33,34] reduce postprandial hyperglycemia. [35] It is rich source of calcium, iron content, [36] less allergenic, digest easily hence it is most suitable for the growing children, females and aged people.…”
Section: Finger Milletmentioning
confidence: 99%
“…This study also elucidated that improved plasma levels of adiponectin and high‐density lipoprotein (HDL) cholesterol could be attained upon feeding proso millet to type 2 diabetic mice. Pradhan et al (2010) reported lowered GI in 13 diabetic human subjects upon consumption of millet‐based chapatti.…”
Section: Effects Of Hydrothermal Processesmentioning
confidence: 99%
“…attained upon feeding proso millet to type 2 diabetic mice Pradhan et al (2010). reported lowered GI in 13 diabetic human subjects upon consumption of millet-based chapatti.Tannins and phytates help in reducing esophageal, colon, and breast cancer Wu et al (2012).…”
mentioning
confidence: 97%